Nano Scale Methods for Water Pollution Monitoring (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article deals with issues related to the textiles coated with metal nanoparticles and detection of the concentrations of released particles in water. The main risks associated with the use of metal covered textiles are detaching of metal nanoparticles from the material during use and care and thus polluting the environment, or inhaled to get in a human or animal body. Nanoparticles can be detached from the textile during washing also, thus polluting the water body and making detriment to the living beings in them. This article aims to look at equipment for nanoparticle size and concentration detection in liquids. Described the world's most popular methods (Microscopy techniques, Photon Correlation Spectroscopy, Nanoparticle Tracking Analysis) and compared to new, alternative method - Gas Discharge Visualization (GDV) electrography. Within the framework of the article analyzed the advantages and disadvantages of each method and estimated the perspective of GDV electrography for detection of metal nanoparticles in water.